APAKAH LEVERAGE DAN PROFITABILITAS DAPAT MENINGKATKAN EARNING RESPONSE COEFFICIENT? - Devi Pujiati Rohmah; Melinda Purnama Kurnia Sari; Moch Rifqi Rizal; Amrie Firmansyah (Polytechnic of State Finance STAN, 2024)
The objective of this study is to assess the impact of leverage and profitability on the Earnings Response Coefficient (ERC). The utilized methodology employs a quantitative approach, utilizing annual data from logistics sector companies listed on the Indonesia Stock Exchange (IDX) for the period spanning from 2020 to 2022. The data were collected from the official IDX website, www.idx.co.id, using purposive sampling techniques. A total of 45 observations were selected for the sample. Panel data was subjected to hypothesis testing using multiple linear regression analysis. The research findings indicate that leverage positively influences ERC, however profitability does not have a significant effect on ERC. This work aims to make a valuable contribution to the existing literature on ERC, particularly in the context of corporate data in the logistics sector, which has received limited attention in earlier research.